Blood Salvage and Autotransfusion With Single Leukoreduction Does Not Increase the Risk of Tumor Recurrence After Liver Transplantation for Advanced Hepatocellular Carcinoma. Issue 6 (18th December 2022) - Kwon, Ji-Hye; Han, Sangbin; Kim, Doyeon; Kuk, Joon Hee; Cho, Hyun; Kim, Seonwoo; Yang, Ju Dong; Kim, Chul; Kim, Jong Man; Choi, Gyu Sung; Joh, Jae-Won; Ko, Justin S.; et al.
Abstract : Objective: The aim of this study was to determine whether autotransfusion of salvaged blood with single leukoreduction is associated with post-transplant tumor recurrence in patients with advanced hepatocellular carcinoma (HCC). Background: Previous studies have consistently demonstrated the safety of autotransfusion of salvaged and leukoreduced blood during liver transplantation for HCC. However, the effects of this technique remained unknown for advanced HCC. Methods: Of 349 patients who underwent living donor liver transplantation for advanced HCC: 74 of 129 without autotransfusion were matched with 74 of 220 with autotransfusion using propensity score based on tumor biology, allogeneic transfusion, and others. Survival analysis was performed with death as a competing risk event. The primary outcome was HCC recurrence. Results: Recipients in autotransfusion group received 811 (497–1247) mL of salvaged blood with single leukoreduction. In the matched cohort, cumulative overall recurrence probability at 1/2/5 years after transplantation was 24.6%/ 38.3%/39.7% for nonautotransfusion group and 16.2%/23.1%/32.5% for autotransfusion group. There were no significant differences between the 2 groups in overall recurrence [hazard ratio (HR) = 0.72 (0.43–1.21)], intrahepatic recurrence [HR = 0.70 (0.35–1.40)], and extrahepatic recurrence [HR = 0.82 (0.46–1.47)]. Also, there were no significant differences in overall death [HR = 0.57 (0.29–1.12)], HCC-related death [HR = 0.59 (0.29–1.20)], and HCC-unrelated death [HR = 0.48 (0.09–2.65)]. Conclusions: When allogeneic transfusion was matched, autotransfusion was not significantly related to HCC recurrence, with more favorable probabilities for autotransfusion, in patients with advanced HCC. Thus, blood salvage and autotransfusion could be safely used with single leukoreduction, without double-filtered leukoreduction, during liver transplantation for HCC with potential benefits from avoiding allogeneic red blood cell transfusion.